Economic Value of Domestic Waste Processing In Puri Cipageran Indah - Widyanto, Bambang Eko; Hasan, Fuad; AshSiddiq, Raden Herdian Bayu; Setiawan, Asep; Akbar, Sandy Radhitya (CENTRAL ASIA AND THE CAUCASUS, 2022)
The In making compost, especially for the household scale, it takes a tool or container called a composter. This composter can be made of plastic barrels or modified cement boxes and placed indoors or outdoors. Here is How to Use Composter. Organic materials referred to in the definition of compost are grass, straw, remnants of twigs and branches, animal manure, fallen flowers, urine of livestock, and other organic materials. All of these organic materials will experience weathering caused by microorganisms that thrive in moist and wet environments. This study is an explain about the economic value of domestic waste processing by a simple waste composting in Puri Cipageran Indah. The waste problem arises because the community care less about managing it. Public still throwing a lot of trash carelessly, especially in residential areas. Dirty environment due to piles and scattered garbage.. Garbage causes pollution of water, soil and air, disturbing health, comfort and unparalleled views delicious.